Inklusi dan Literasi Keuangan (Studi pada Masyarakat Kota Surabaya) - Murtadho, Muis (UNUSA Press, 2016)
This research is a survey conducted on 500 people in the city of Surabaya. The purpose of this research was to assess the level of financial inclusion and financial literacy in the community of Surabaya City. So it can be known how much knowledge people of Surabaya towards the use of products services banking and financial institutions. This Research was conducted in the community of Surabaya City, because Surabaya is a business city and trading town in East Java. This research method using descriptive qualitative research that can be clearly describe on the level of financial inclusion and financial literacy in the community of Surabaya City. The results of this research are the level of financial inclusion in the community of Surabaya City is very high at 73.6% and level of financial literacy shows excellent condition in which the community knowledge about the products of financial institutions is quite good and can be implemented well.